Magnetic Studies of Redox‐Active Tetrathiafulvalene‐Based Complexes: Dysprosium vs. Ytterbium Analogues. Issue 24 (21st March 2014) - Jung, Julie; da Cunha, Tamyris T.; Le Guennic, Boris; Pointillart, Fabrice; Pereira, Cynthia L. M.; Luzon, Javier; Golhen, Stéphane; Cador, Olivier; Maury, Olivier; Ouahab, Lahcène
Abstract: The two mononuclear complexes [Ln(tta)3 (L)]· C6 H14 {Ln = Dy III and Yb III } (tta – = 2‐thenoyltrifluoroacetonate, L = 2‐{1‐methylpyridyl‐4, 5‐[4, 5‐bis(propylthio)tetrathiafulvalenyl]‐1 H ‐benzimidazol‐2‐yl}pyridine) are isostructural. The lanthanide ions adopt a distorted‐square‐antiprism coordination polyhedron ( D 4d symmetry). The Dy III compound behaves like a single‐molecule magnet (SMM), whereas no out‐of‐phase component of the magnetic susceptibility is measured for Yb III . The crystal‐field splitting of the 2 F7/2 and 6 H15/2 ground multiplets of Yb III and Dy III, respectively, were determined by means of ab initio calculations and confirmed by the emission energy lines of the 2 F5/2 → 2 F7/2 luminescence spectrum in the case of Yb III . The nature of the MJ ground states indicates that Yb III is not an Ising system, whereas Dy III is. The experimental and calculated anisotropy axes for Dy III lie along the most negatively charged direction, whereas those for Yb III lie almost perpendicularly. Finally, the gz values corroborate the uniaxiality of the anisotropy axis for Dy III . Abstract : The crystal‐field energy splitting of the ground‐state multiplets of the complexesDy andYb was evaluated, and they demonstrate Ising and non‐Ising character. Both anisotropy axis directions for the MJ ground states were determined in agreement with the oblate and prolate electronic distribution for Dy III and Yb III ions. This results in SMM and non‐SMM behaviour forDy andYb, respectively.